Social Empathy and Emotional Control In Shaping Stop Bullying Behavior Among Salafiyah Ulya Students At Pondok Pesantren Al-Madina Al-Islami Prabumulih - Rahmat Dipuro; Edy Purwanto; Saukani Nur Akbar; Benny Prasetiya (INNOVASI : JURNAL INOVASI PENDIDIKAN, 2026)
This study aimed to analyze the role of social empathy and emotional control in shaping stop bullying behavior among Salafiyah Ulya santri at Pondok Pesantren Al-Madina Al-Islami Prabumulih. The study employed a qualitative approach with a phenomenological design to understand students’ subjective experiences related to social interaction, emotional regulation, and stop bullying culture within the daily life of the pesantren environment. Research participants consisted of the pesantren leader, ustadz, dormitory supervisors musyrif, and santri selected through purposive sampling. Data were collected through semi-structured in-depth interviews, participant observation, and documentation. Data analysis utilized the interactive model of Matthew B. Miles and A. Michael Huberman, including data reduction, data display, and conclusion drawing, while data validity was ensured through source triangulation, technique triangulation, and member checking. The findings revealed that students social empathy developed through collective dormitory life, which fostered solidarity, social concern, and emotional support among santri. The most commonly identified form of bullying was verbal bullying, particularly ridicule and excessive joking, although its intensity remained relatively low. The pesantren culture, which emphasizes ukhuwah Islamiyah (Islamic brotherhood), mutual respect, and the practice of reminding one another, also functioned as a mechanism of social control in creating a safe and harmonious environment.